DAMPAK KETIDAKSINKRONAN GATE TERHADAP ALUR KEBERANGKATAN DAN CUSTOMER EXPERIENCE PENUMPANG DI TERMINAL 1 BANDARA INTERNASIONAL JUANDA - Muhammad Wildan Sururi; Tri Kartika Pertiwi (Al-Ijtimā': Jurnal Pengabdian Kepada Masyarakat, 2025)
The dynamics of airport operational activities often lead to discrepancies between scheduled and actual departure times, particularly in cases of flight delays. One of the resulting implications is the lack of synchronization in gate boarding assignments at Terminal 1 of Juanda International Airport, which affects the clarity of information and passenger convenience. This article aims to describe the factors contributing to gate boarding discrepancies and to analyze their impact on departure flow and passenger experience. The study employs a qualitative descriptive method, with data collected through direct observation and interviews with Terminal Inspection Services (TIS) personnel involved in gate management. The findings indicate that airline operational delays, limitations of the Flight Information Display System (FIDS), the implementation of a less adaptive dedicated gate system, and inconsistencies between boarding gates and aircraft parking stands are the main factors influencing the effectiveness of departure services. These findings highlight the importance of improving operational coordination and implementing more flexible gate management systems to support smoother departure processes and enhance overall passenger service quality at the airport.